Successful Management of Panuveitis and Associated Complications in a Patient with Clinical Stage III HIV: A Case Report - Putra, Ikhsan Amanda; Fadrian; Rohayat Bilmahdi (HM Publisher, 2024)
Background: Human immunodeficiency virus (HIV) infection can lead to a myriad of ocular complications, including panuveitis, an inflammatory condition affecting the entire uvea and surrounding structures. The management of panuveitis in HIV patients is complex, often requiring a multidisciplinary approach to address both the underlying immunodeficiency and the ocular inflammation. Case presentation: We present the case of a 37-year-old male patient with clinical stage III HIV who presented with panuveitis in the right eye (OD) secondary to herpes zoster ophthalmicus (HZO). The patient also had post-herpetic neuralgia, oral candidiasis, and malnutrition. He reported a history of unprotected sexual encounters with multiple partners. The patient's CD4 count was critically low at 15 cells/µL, indicating severe immunosuppression. He was initiated on antiretroviral therapy (ART), prophylactic medications to prevent opportunistic infections, and pain management for post-herpetic neuralgia. Conclusion: This case highlights the challenges in managing panuveitis and associated complications in patients with advanced HIV infection. Early diagnosis, prompt initiation of ART, and a multidisciplinary approach are crucial for successful management and improving patient outcomes.